Differences in ovarian aging patterns between races are associated with ovarian genotypes and sub-genotypes of the FMR1 gene - Gleicher Norbert; Kim Ann; Weghofer Andrea; Barad David H (BMC, 2012)
Abstract Background Ovarian aging patterns differ between races, and appear to affect fertility treatment outcomes. What causes these differences is, however, unknown. Variations in ovarian aging patterns have recently been associated with specific ovarian genotypes and sub-genotypes of the FMR1 gene. We, therefore, attempted to determine differences in how functional ovarian reserve (FOR) changes with advancing age between races, and whether changes are associated with differences in distribution of ovarian genotypes and sub-genotypes of the FMR1 gene. Methods We determined in association with in vitro fertilization (IVF) FOR in 62 young Caucasian, African and Asian oocyte donors and 536 older infertility patients of all three races, based on follicle stimulating hormone (FSH), anti-Müllerian hormone (AMH) and oocyte yields, and investigated whether differences between races are associated with differences in distribution of FMR1 genotypes and sub-genotypes. Results Changes in distribution of mean FSH, AMH and oocyte yields between young donors and older infertility patients were significant (all P < 0.001). Donors did not demonstrate significant differences between races in AMH and FSH but demonstrated significant differences in oocyte yields [F(2,59) = 4.22, P = 0.019]: Specifically, African donors demonstrated larger oocyte yields than Caucasians (P = 0.008) and Asians (P = 0.022). In patients, AMH levels differed significantly between races [F (2,533) = 4.25, P = 0.015]. Holm-Sidak post-hoc comparisons demonstrated that Caucasians demonstrated lower AMH in comparison to Asians (P = 0.007). Percentages of FMR1 genotypes and sub-genotypes in patients varied significantly between races, with Asians demonstrating fewer het-norm/low sub-genotypes than Caucasians and Africans (P = 0.012). Conclusion FOR changes in different races at different rates, and appears to parallel ovarian FMR1 genotypes and sub-genotype distributions. Differences in ovarian aging between races may, therefore, be FMR1-associated.